Optimalisasi Literasi Siswa Sekolah Dasar melalui Metode Project Based Learning: Kajian Literatur Sistematis - Aulianesia, Bunga; Aryanto, Sani; Yohamintin, Yohamintin; Gumala, Yosi (IAIN Kendari, 2024)
The literacy level of primary school students in Indonesia remains relatively low, as reflected in international reports such as PISA. This study aims to examine the effectiveness of the Project-Based Learning (PjBL) method in enhancing literacy skills among primary school students. Employing a Systematic Literature Review (SLR) approach based on the PRISMA guidelines, the study analyzed 09 selected articles out of 89 identified publications. These articles were selected through strict inclusion and exclusion criteria and analyzed using thematic synthesis. The findings indicate that PjBL is effective in improving basic literacy skills in lower grades through simple, child-relevant projects such as creating miniatures or storytelling with pictures. In upper grades, PjBL has been shown to foster higher-order thinking skills, digital literacy, and student creativity through more complex and collaborative projects. The main challenges in implementing this method include limited facilities, lack of accessible reading materials, and teacher preparedness in designing and facilitating project-based learning. Thus, PjBL is an innovative, relevant, and adaptive approach for enhancing the literacy quality of primary school students. To ensure optimal effectiveness, educational infrastructure support, teacher training, and the development of flexible and contextual curricula are required.Keywords: Literacy, project-based learning, primary school students, critical thinking, creativity.